A(rt)ssenede '89. (Assenede : V.Z.W. A(rt)ssenede, 1989)
Ampe, Dominique ; Baeyens, Martine ; Balder ; Borsten, Henric ; Brandts, Eric ; Cambeen, Albert ; Cavens, Frit ; Celie, Pieter ; Claus, Elly ; Cocken, Anne ; Cornelis, Beniti ; Crab, Jan ; Cuvelier, Werner ; De Baudringhien, Filip ; Degreve, Maria ; Demuysere, Marie-Ange ; De Roover, Marc ; De Ruyter, Hans ; De Waele, Coenraed ; Dey, Han ; D'Hondt, Lieve ; Dierickx, Karel ; Dijck, Ward ; Dusepulchre, Francis ; Eggermont, Carlo ; Elia, Elie ; etc.
A(rt)ssenede '89, Gemeente Assenede, 1989
boek